1941
DOI: 10.1021/jo01202a010
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON LACTONES RELATED TO THE CARDIAC AGLYCONES. I. SYNTHESIS OF β-SUBSTITUTED Δα,β-BUTENOLIDES FROM ι-METHOXYMETHYL KETONES

Abstract: The group of naturally occurring substances known as the cardiac drugs forms an interesting division of the large group of steroids. These substances have been grouped together on the basis of a common pharmacodynamic action on the heart. The investigations, chiefly of Jacobs, Windaus, Tschesche, and Stoll, have provided ample evidence, which has been adequately reviewed in numerous publications (1), for assigning structures to the more important members of the group. With the exception of the toad venoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

1941
1941
2011
2011

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…In order to circumvent the difficult dehydration of the hydroxy acetal ester, II, ethyl /3-methylcinnamate (VIII) was oxidized with selenium dioxide, with the object of taking advantage of the activation of the hydrogens of the methyl group by the double bond and thus proceeding directly to the unsaturated aldehydo ester III. However, the oxidation proceeded only to the alcohol stage (IX), and the only product isolated was the ® ^-lactone V. This experiment is of significance, however, in that it provides rigid confirmatory evidence for the structure assigned to this lactone both in this paper and in a preceding one (1).…”
Section: C6h6coch(ohsupporting
confidence: 64%
See 1 more Smart Citation
“…In order to circumvent the difficult dehydration of the hydroxy acetal ester, II, ethyl /3-methylcinnamate (VIII) was oxidized with selenium dioxide, with the object of taking advantage of the activation of the hydrogens of the methyl group by the double bond and thus proceeding directly to the unsaturated aldehydo ester III. However, the oxidation proceeded only to the alcohol stage (IX), and the only product isolated was the ® ^-lactone V. This experiment is of significance, however, in that it provides rigid confirmatory evidence for the structure assigned to this lactone both in this paper and in a preceding one (1).…”
Section: C6h6coch(ohsupporting
confidence: 64%
“…Better success attended the application of the Reformatzky reaction to the acetal of phenylglyoxal, although in comparison with the methods presented in earlier papers (1,2) this scheme possesses serious disadvantages. Nevertheless, it seems of interest to present at this time our experiences dealing with phenylglyoxal and its derivatives, in view of the experiments along the same line recently reported by Shemyakin and Red'kin (7).…”
mentioning
confidence: 99%
“…In a preceding paper (19) the synthesis of model ß-substituted Aa '0-butenolides has been described. A study of the properties of ß-cyclohexyl-" -M)utenolide has revealed information which has led us to consider more seriously the question of a "'^-formulation for the unsaturated lactones of the natural cardiac drugs.…”
mentioning
confidence: 99%
“…A small test portion of the crystalline material was removed and the accompanying oil was drained off on a porous plate. The remaining crystalline material gave a strong nitroprusside reaction and was identified as /3-phenyl-A">s-butenolide by mixed melting point (4). It was impossible to isolate the oily hydroxy lactone in a pure state since this lost water very easily on manipulation.…”
mentioning
confidence: 99%
“…A small portion of the crystalline material was removed from the mixture, freed from accompanying oil by pressing on a porous plate, and recrystallized from water. The crystalline material melted at 112°and gave no depression with /3-cyclohexyl-(3-hydroxybutyrolactone prepared from methoxymethylcyclohexyl ketone (4). It was neutral, saturated towards catalytically activated hydrogen and gave negative Tollens' and nitroprusside color tests.…”
mentioning
confidence: 99%